Simultaneous biventricular pressure-volume analysis in rats - Miklovic, M; Kala, P; Melenovsky, V (Journal of physiology and pharmacology, 2023)
The pressure-volume (PV) analysis is used for an accurate assessment of load-independent cardiac function and is important for the study of cardiovascular diseases and various therapeutic modalities. PV analysis is often performed on one of the ventricles, or on both ventricles but sequentially. Since both ventricles interact with each other and their functions are mutually interdependent, especially in various disease conditions such as pulmonary hypertension or heart failure, it is important to quantify the function of both ventricles at the same time. Therefore, our aim was to describe a standardized protocol for simultaneous right (RV) and left (LV) ventricle of PV analysis, including an especially controllable preload reduction manoeuver. Our second aim was to test whether simultaneous catheterization of both LV and RV is necessary for the determination of biventricular PV relationship compared to sequential measurement of both ventricles separately. In this article, we showed the feasibility and the value of simultaneous biventricular PV analysis in the measurement of contractility parameters (end-systolic pressure-volume relationship (ESPVR), ventricular pressure over time (dP/dt)max, divided by end-diastolic volume (dP/dt max-EDV)) with a comparison to the sequential measurement of the RV and LV ventricles separately. We described in detail the protocol for simultaneous biventricular PV analysis in rats using a pair of conductance-micromanometer catheters with a preload-reducing manoeuver using balloon catheter inflation in the inferior vena cava. We also described technical tips and show examples of PV loop data obtained in normotensive and hypertensive rats, with and without heart failure due to volume overload. This protocol could be useful for scientists studying hemodynamics and cardiac contractility in various models of cardiovascular diseases with a focus on biventricular differences and ventricular interdependence.
Keywords: kontrakce myokardu; hemodynamika; srdeční selhání; kardiovaskulární nemoci; krysa rodu Rattus; Heart Failure; Animals; srdeční komory; Rats; zvířata; Hemodynamics; Heart Ventricles; Cardiovascular Diseases; Myocardial Contraction